2021
DOI: 10.1002/acn3.51420
|View full text |Cite
|
Sign up to set email alerts
|

JKAP relates to disease risk, severity, and Th1 and Th17 differentiation in Parkinson's disease

Abstract: Objective JNK pathway‐associated phosphatase (JKAP) is previously reported to regulate immune/inflammatory process via T‐cell signaling, and closely involves in neurological diseases, while its implication in Parkinson's disease (PD) is unknown. Therefore, this study aimed to investigate the correlation of JKAP with Th1/Th2/Th17 cells and their clinical roles in PD patients, and then further explore the effect of JKAP on regulating CD4+ T‐cell differentiation in PD. Methods Totally 50 PD patients and 50 age‐/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
(44 reference statements)
0
21
0
Order By: Relevance
“… 15 It is also revealed that in asthmatic exacerbation children, DUSP22 negatively associates with eosinophil count and immunoglobulin E. 16 Besides, DUSP22 is negatively correlated with Unified Parkinson's Disease Rating Scale (UPDRS)‐I score and UPDRS‐III score in Parkinson patients. 17 In our study, we discovered that DUSP22 was negatively associated with PASI score and positively correlated with history of systemic biologic treatment in psoriasis patients. Possible reasons might be that: (1) DUSP22 could suppress T‐cell activation and the proliferation of CD4 + T cells through JNK pathway, 14 which would alleviate inflammation and subsequently result in less serious skin lesion in psoriasis; DUSP22 could suppress the activity of T‐cell immune response, which played an important role in the function of keratinocytes, then further slowing down the aberrant proliferation of keratinocytes and causing a lower disease activity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 57%
“… 15 It is also revealed that in asthmatic exacerbation children, DUSP22 negatively associates with eosinophil count and immunoglobulin E. 16 Besides, DUSP22 is negatively correlated with Unified Parkinson's Disease Rating Scale (UPDRS)‐I score and UPDRS‐III score in Parkinson patients. 17 In our study, we discovered that DUSP22 was negatively associated with PASI score and positively correlated with history of systemic biologic treatment in psoriasis patients. Possible reasons might be that: (1) DUSP22 could suppress T‐cell activation and the proliferation of CD4 + T cells through JNK pathway, 14 which would alleviate inflammation and subsequently result in less serious skin lesion in psoriasis; DUSP22 could suppress the activity of T‐cell immune response, which played an important role in the function of keratinocytes, then further slowing down the aberrant proliferation of keratinocytes and causing a lower disease activity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, JKAP was negatively associated with disease severity in AIS patients. (ii) Sudden onset of focal neurological deficit facilitated disease severity of AIS patients, while JKAP could ameliorate neuronal function through stimulating neuron viability 2,15 . Thus, JKAP was negatively related to disease severity in AIS patients.…”
Section: Discussionmentioning
confidence: 96%
“…2,15 Thus, JKAP was negatively related to disease severity in AIS patients. (iii) As mentioned above, JKAP alleviated inflammation level and disease severity in AIS patients, while recurrence patients…”
mentioning
confidence: 99%
“…Since DUSP22 is a regulator of T‐cell activation and differentiation, the correlation of blood DUSP22 dysregulation with inflammation is identified in several diseases featured by dysregulated immune or inflammation. 12 , 20 , 21 , 24 , 25 , 26 , 27 For instance, serum DUSP22 relates to decreased CRP, number of joints with active arthritis, physician's global assessment of disease activity in juvenile idiopathic arthritis patients. 25 In addition, serum DUSP22 correlates with less sever inflammation and disease activity in Crohn disease patients.…”
Section: Discussionmentioning
confidence: 99%